Fiduciary Duties of Directors in the Management of State-Owned Enterprises : Case Study of PT Timah Tbk - Rohatta, Helly; Sodikin, Sodikin (CV. ULIL ALBAB CORP, 2025)
Law Number 16 of 2025 introduces a new governance framework for State-Owned Enterprises (SOEs) in Indonesia by strengthening the Business Judgment Rule (BJR) doctrine and establishing BPI Danantara as a state-owned legal entity with significant authority over national investments. This study aims to construct the concepts of fiduciary duty and the Business Judgment Rule within the context of Law No. 16 of 2025, focusing on how these regulations can prevent the abuse of authority, as seen in the case of PT Timah. The research method employed is descriptive-analytical, which serves to outline the development of regulations and their implications for improving SOE governance practices within the Indonesian legal system. The findings indicate that Law No. 16 of 2025 establishes a new governance paradigm for State-Owned Enterprises, mainly through the codification of the Business Judgment Rule (BJR) and the creation of BPI Danantara as a state investment superholding with strategic authority. Additionally, this law provides legal protection for decision-makers, provided their actions are conducted in good faith, with prudence, free from conflicts of interest, and in the best interests of the company. Nevertheless, this research highlights that the expansion of legal immunity should be strictly interpreted within the context of fiduciary duty, as SOEs manage public assets and are not solely focused on profit generation.